Ultrasonic Pre-Treatment and Vacuum Effect on the Drying of Cancer Pagurus Meat - Ozyalcin, Zehra Ozden; Kipcak, Azmi Seyhun (ISTANBUL UNIV PRESS, FAC AQUATIC SCIENCES, 2023)
This study investigates the impacts of vacuum and ultrasonic pre-treatment on drying kinetics, mathematical modeling, and color changes of Cancer pagurus (brown crab). The Midilli & Kucuk model provided the best match for all the drying techniques examined. Using a variety of drying techniques such as oven drying (OD), vacuum oven drying (VOD), ultrasonic pre-treated oven drying (US-OD), and ultrasonic pre-treated vacuum oven drying (US-VOD), effective moisture diffusivities (Deff) and activation energies (Ea) were calculated. According to the findings of the study, vacuum and ultrasonic pretreatment shortened drying times, which is crucial for improving drying effectiveness and lowering costs. On the other hand, the OD method had the lowest Deff values (0.397-0.673 x 10-10 m2/s), indicating that it was the least efficient method for removing moisture. The study also found that the highest Ea value was observed in the US-VOD method (44.60 kJ/mol) and the lowest in the OD method (25.69 kJ/mol). Interestingly, the US-VOD method also had the lowest & UDelta;E values (17.09 - 20.33), indicating that both US pre-treatment and vacuum application were successful in preserving the color of the brown crab.
Keywords: Crab; oven; seafood; ultrasonic pre-treatment; vacuum oven; KINETICS; SLICES; Marine & Freshwater Biology